Physarum can compute shortest paths: A short proof - Bonifaci, Vincenzo (Information processing letters, 2013)
The purpose of this note is to give a short proof that a standard model for the Physarum polycephalum slime mold correctly computes the shortest path in an undirected weighted graph [V. Bonifaci, K. Mehlhorn, G. Varma, Physarum can compute shortest paths, in: Proc. of the 23rd ACM–SIAM Symposium on Discrete Algorithms, SIAM, 2012, pp. 233–240]. ► Physarum is a slime mold giving rise to a “natural algorithm” for the shortest path problem. ► A standard model for Physarum converges to the shortest path in any network. ► Very mild assumptions on the input data allow for a much shorter proof of convergence.